2012
DOI: 10.1071/eg11022
|View full text |Cite
|
Sign up to set email alerts
|

Lower crust and upper mantle electrical anisotropy in southeastern Australia

Abstract: The dominant north-south strike of the Palaeozoic outcrop of central Victoria has been well documented, but to the north, these rocks are covered by the Cainozoic sedimentary deposits of the Murray Basin. Two magnetotelluric surveys were completed to assist in extrapolation of the known structure and to identify possible new targets for mineral discovery. Supporting the results from previous seismic interpretations for the region, the 2D MT inversion models substantiate an intrazone thrust fault system of list… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A deep mantle conductor is situated underneath the central Gawler Craton and appears to be temporally related to the 1590Ma Hiltaba event and Gawler Range Volcanics, which are the result of a plume‐modified orogenesis as an analogue to present day Yellowstone‐type magmatism [ Kelbert et al , ]. Further studies will need to address the depth extent of the conductor to depths beyond 100km and possible anisotropy of the mantle given the strong electrical polarization state derived from phase tensor analysis in this study and from recent findings in other areas of the Australian continent [ Simpson , ; Dennis et al , ] (Figure ). The mantle is resistive underneath the St. Peter Suite, Fowler Domain and the 2550 Ma Mulgathing Complex suggesting a more depleted mantle in those parts.…”
Section: Discussionmentioning
confidence: 99%
“…A deep mantle conductor is situated underneath the central Gawler Craton and appears to be temporally related to the 1590Ma Hiltaba event and Gawler Range Volcanics, which are the result of a plume‐modified orogenesis as an analogue to present day Yellowstone‐type magmatism [ Kelbert et al , ]. Further studies will need to address the depth extent of the conductor to depths beyond 100km and possible anisotropy of the mantle given the strong electrical polarization state derived from phase tensor analysis in this study and from recent findings in other areas of the Australian continent [ Simpson , ; Dennis et al , ] (Figure ). The mantle is resistive underneath the St. Peter Suite, Fowler Domain and the 2550 Ma Mulgathing Complex suggesting a more depleted mantle in those parts.…”
Section: Discussionmentioning
confidence: 99%
“…This conductor extends beyond the edge of the profile, and an extension of the profile to the west of the transect, and longer period data would be required to have any confidence in interpretations of the anomaly. The Mt Gambier volcanoes are 100- Dennis et al (2012). This feature was thought to be connected to a central Victorian thermal anomaly and mantle-derived CO 2 -rich fluids related to the Quaternary Newer Volcanics, but required further thermal modelling.…”
Section: Interpreting the Conductorsmentioning
confidence: 97%
“…The Geological Structure data map for the study area is shown in Figure 2d. A preliminary interpretation report on the area was produced by the Korean Institute of Geological & Mineral Resources (KIGAM) as part of a collaborative project among GSV, Monash University and KIGAM (Dennis et al., 2012). The Geological Structure Map provided by GSV originally included 34 geological categories (e.g.…”
Section: Study Area Data and Mapsmentioning
confidence: 99%
“…The data is gridded with a grid size of 50 m, using a minimum curvature gridding method. The final merged grid is presented as two zonally projected grids (Cull et al, 2008;Dennis et al, 2008Dennis et al, , 2012.…”
Section: Plain Language Summarymentioning
confidence: 99%